Differences Between Centers in Psychosocial Evaluations for Living Kidney Donors Do Not Influence Outcome: Results From an Observational Multicenter Study. Issue 12 (4th November 2022) - Ludwig, Gundula; Geiger, Irene; Götzmann, Lutz; Jordan, Katja-Daniela; Döbbel, Susanne; Klaghofer, Richard; Salathé, Michelle; Stillhard, Urs; Meinlschmidt, Gunther; Kiss, Alexander; Venetz, Jean-Pierre; Steiger, Jürg; et al.
Abstract : Background: Rather little is known about how psychosocial evaluations for living kidney donation (LKD) are performed. We aimed to explore whether Swiss transplant centers (STCs) vary regarding the rate of living kidney donors refused for psychosocial reasons, the psychosocial evaluation process, and the characteristics of the donors. Methods: We investigated 310 consecutive candidates for LKD in 4 of 6 existing STC during mandatory psychosocial evaluations. We registered (i) sociodemographic data, (ii) the type of the decision-making process regarding LKD (ie, snap decision, postponed, deliberate, other), (iii) the evaluator's perception of the donor's emotional bonding and his/her conflicts with the recipient, (iv) the donor's prognosis from a psychosocial perspective, (v) time taken for the psychosocial evaluation, and (vi) its result (eligible, eligible with additional requirements, not eligible). Results: Centers had comparable proportions of noneligible donors (2.9%–6.0%) but differed significantly in the percentage of donors accepted with additional requirements (3.4%–66%, P  < 0.001). Significant differences emerged between centers regarding the time needed for evaluation (75–160 min [interquartile range (IQR) 75–180 min] per single exploration, P  < 0.001), the perception of the donor's emotional bonding (visual analogue scale [VAS] 8–9 [IQR 6–10], P  < 0.001), his/her conflicts with the recipient (VAS 1.5–2 [IQR 0–3], P  = 0.006), the donor's psychosocial prognosis (VAS 8–9 [IQR 7–10], P  < 0.001), and the type of decision concerning LKD (59%–82% with snap decision "yes, " P  = 0.008). However, despite differences in the psychosocial evaluation process, the rates of patients accepted for transplantation (eligible and eligible with additional requirements versus noneligible) were comparable across STC ( P  = 0.72). Conclusions: Our results emphasize that it is more important to establish clear guidelines to identify potential psychosocial risks than to stringently standardize the procedure for psychosocial evaluation of living kidney donors.